Effects of oncoming vehicle size on overtaking judgments. (September 2015) - Levulis, Samuel J.; DeLucia, Patricia R.; Jupe, Jason
Highlights: Participants made overtaking judgments in a driving simulator. Oncoming motorcycles resulted in more accepted gaps than cars or trucks. Smaller vehicles resulted in more accepted gaps than larger vehicles. Judgments did not differ between active overtaking and passive judgments. Drivers may misjudge the distances of motorcycles due to their small sizes. Abstract: During overtaking maneuvers on two-way highways drivers must temporarily cross into the opposite lane of traffic, and may face oncoming vehicles. To judge when it is safe to overtake, drivers must estimate the time-to-contact (TTC) of the oncoming vehicle. Information about an oncoming vehicle's TTC is available in the optical expansion pattern, but it is below threshold during high-speed overtaking maneuvers, which require a large passing distance. Consequently, we hypothesized that drivers would rely on perceived distance and velocity, and that their overtaking judgments would be influenced by oncoming vehicle size. A driving simulator was used to examine whether overtaking judgments are influenced by the size of an oncoming vehicle, and by whether a driver actively conducts the overtaking maneuver or passively judges whether it is safe to overtake. Oncoming motorcycles resulted in more accepted gaps and false alarms than larger cars or trucks. Results were due to vehicle size independently of vehicle type, and reflected shifts in response bias rather than sensitivity. Drivers may misjudge the distances of motorcycles due to their relatively small sizes, contributing to accidents due to right-of-way violations. Results have implications for traffic safety and the potential role of driver-assistance technologies.